Effect of enzymatic transesterification using Mucor miehei lipase on physicochemical properties of engkabang (Shorea macrophylla) fat - canola oil blends - Mohamed Roslan, Nur Illiyin; Marikkar, Jalaldeen Mohammed Nazrim; Abdul Manaf, Yanty Noorzianna; Mustafa, Shuhaimi; Mat Sahri, Miskandar (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2019)
The effect of transesterification of engkabang (Shorea macrophylla) fat - canola oil (EF35/CaO65) blend by Mucor miehei lipase (1%, w/w oil) in a solvent-free system was investigated at different time intervals of 6 h, 12 h and 24 h. Compositional changes of the samples withdrawn at specified time intervals while the reaction in progress were analysed by chromatography, whereas the polymorphic forms and thermal properties were analysed by using X-ray diffraction and differential scanning calorimetry, respectively. There were increases in the amounts of monounsaturated and triunsaturated triacylglycerol (TAG) molecular groups with concurrent reductions of the proportions of desaturated TAG molecular groups during different time intervals. This changing TAG composition led to changes in crystallisation behaviour and thermal properties of the samples, reducing some enthalpy values. All samples withdrawn at different time intervals displayed both β' and β type crystal polymorphs even though engkabang fat itself was predominantly β‐type. In terms of melting, solidification and polymorphic properties, the sample withdrawn at 6 h time interval was found to display the closest similarity to lard (LD).